Enhancing Reading Abilities: Analysis of Blended Project Based Learning by Integrating Instagram and Google Classroom - Yuniar, Rendhi Fatrisna; Khatami, Muhammad; Tarbiyah, Shofwatut; Nabillah, Yumnaa Taqiyatul (SCOPE: Journal of English Language Teaching, 2025)
In this era, education in Indonesia tends to be low compared to other countries. One of the causes of the lack of advancement of education in our country is the need for more interest in reading or literacy in students both from elementary school level to university students. This study investigates the effectiveness of Blended Project-Based Learning through the integration of Instagram and Google Classroom, employing a quasi-experimental design. The primary objective was to assess whether the Blended PBL approach leads to greater improvements in students' reading skills compared to traditional instructional methods. The research was conducted with 50 second-semester English Education Department students at UIN Malang. This study involved two groups: an experimental group that engaged in Blended PBL and a control group that followed conventional teaching practices. Reading proficiency was measured using pre-test and post-test assessments. The data analysis conducted was normality test, homogeneity, and independent sample t-test. The findings indicate a significant improvement in the reading skills of students in the experimental group, as opposed to those in the control group. These results suggest that integrating social media platforms, such as Instagram, alongside digital learning environments like Google Classroom, within a Blended Project-Based Learning framework, can substantially enhance reading comprehension in higher education contexts.